Oestradiol Contributes to Differential Antitumour Effects of Adjuvant Zoledronic Acid Observed Between Pre- and Post-Menopausal Women - Canuas-Landero, Victor G.; George, Christopher N.; Lefley, Diane V.; Corness, Hannah; Muthana, Munitta; Wilson, Caroline; Ottewell, Penelope D. (Frontiers in Endocrinology, 2021)
Clinical trials have demonstrated that adding zoledronic acid (Zol) to (neo)adjuvant standard of care has differential antitumour effects in pre- and post-menopausal women: Both benefit from reduced recurrence in bone; however, while postmenopausal women also incur survival benefit, none is seen in premenopausal women treated with adjuvant bisphosphonates. In the current study, we have used mouse models to investigate the role of oestradiol in modulating potential antitumour effects of Zol. Pre-, peri-, and post-menopausal concentrations of oestradiol were modelled in BALB/c wild-type, BALB/c nude, and C57BL/6 mice by ovariectomy followed by supplementation with oestradiol. Mice also received 40 mg/kg/day goserelin to prevent ovariectomy-induced increases in follicle-stimulating hormone (FSH). Metastasis was modelled following injection of MDA-MB-231, 4T1, or E0771 cells after ovariectomy and saline or 100 μg/kg Zol administered weekly. Supplementing ovariectomised mice with 12.5 mg/ml, 1.38 mg/ml, and 0 ng/ml oestradiol, in the presence of goserelin, resulted in serum concentrations of 153.16 ± 18.10 pg/ml, 48.64 ± 18.44 pg/ml, and 1.00 ± 0.27 pg/ml oestradiol, which are equivalent to concentrations found in pre-, peri-, and post-menopausal humans. Osteoclast activity was increased 1.5–1.8-fold with peri- and post-menopausal compared with premenopausal oestradiol, resulting in a 1.34–1.69-fold reduction in trabecular bone. Zol increased trabecular bone in all groups but did not restore bone to volumes observed under premenopausal conditions. In tumour-bearing mice, Zol reduced bone metastases in BALB/c (wild-type and nude), with greatest effects seen under pre- and post-menopausal concentrations of oestradiol. Zol did not affect soft tissue metastases in immunocompetent BALB/c mice but increased metastases 3.95-fold in C57BL/6 mice under premenopausal concentrations of oestradiol. In contrast, Zol significantly reduced soft tissue metastases 2.07 and 4.69-fold in immunocompetent BALB/c and C57BL/6 mice under postmenopausal oestradiol, mirroring the results of the clinical trials of (neo)adjuvant bisphosphonates. No effects on soft tissue metastases were observed in immunocompromised mice, and differences in antitumour response did not correlate with musculoaponeurotic fibrosarcoma (MAF), macrophage capping protein (CAPG), or PDZ domain containing protein GIPC1 (GIPC1) expression. In conclusion, oestradiol contributes to altered antitumour effects of Zol observed between pre- and post-menopausal women. However, other immunological/microenvironmental factors are also likely to contribute to this phenomenon.